Airlanggon A, a new isoprenylated benzoic acid fromthe roots of Erythrinasu bumbrans and their antioxidant and antimalarial activities - Tjahjandarie, Tjitjik Srie (Scholars Research Library, 2015)
This research was aimed to determine the antioxidant and antimalarial activities from a new isoprenylated benzoic acid, airlanggon A (1) isolated from the roots of Erythrina subumbranstogether with known compounds, methyl 4,6- dihydroxy-2,5-dimethyl benzoic acid (2) and 8-hydroxy-7,4’-dimethoxy isoflavone (3) from the stem barkof E. subumbrans. The structure of three compounds were elucidated by UV, IR, 1D and 2D NMR, and HR-ESI-MS spectra. Compounds 1-3 were evaluated for their antimalarial and antioxidant properties against P. falciparum and DPPH radical scavenging activities.Compounds 1–3 showing their antimalarial activity against P. falciparum with IC50 of 1.98; 1.67 and 1.64 μg/mL and antioxidant properties against DPPH, showing their IC50of 266.48 ; 34.61 and 22.33 μg/mL respectively.The results indicate that 8-hydroxy-7,4’-dimethoxy isoflavone (3) slightly more active thanmethyl 4,6-dihydroxy-2,5-dimethyl benzoic acid (2)and airlanggon A (1) showed moderate activities.